Reforming the international financial system : crisis prevention and response - Teunissen, Jan Joost (FONDAD The HagueNL, 2000)
Examines positive and negative aspects of recent reform proposals. Looks at a new framework for private sector involvement in crisis prevention and management. Discusses recent initiatives to improve the regulation and suspension of private capital flows. Focuses on current proposals to reform the IMF to make it more effective, transparent and accountable.